2018
DOI: 10.4000/remi.10768
|View full text |Cite
|
Sign up to set email alerts
|

L’interprétariat en santé mentale : divisions sociale, morale et spatiale du travail dans les soins aux migrants

Abstract: Revue européenne des migrations internationales vol. 34 -n°2 et 3 | 2018La santé mentale en migrations internationales L'interprétariat en santé mentale : divisions sociale, morale et spatiale du travail dans les soins aux migrants Interpretation in Mental Health Services: Social, Moral and Spatial Divisions of Work in Migrant Care La interpretación en la salud mental: divisiones sociales, morales y espaciales en el trabajo de atención al migrante

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…Twenty publications discussed the impact of the low availability of adequate interpretation services on mental health access and service quality (Asgary & Segar, 2011; Bischoff et al, 2003; Blakely, 1996; Fegert et al, 2018; Fondacaro & Harder, 2014; Forrest-Bank, Held, & Jones, 2019; Hémono et al, 2018; Jensen, Norredam, Priebe, & Krasnik, 2013; Morland, Duncan, Hoebing, Kirschke, & Schmidt, 2005; Pian, Hoyez, & Tersigni, 2018). Studies from Greece (Hémono et al, 2018), New Zealand (Blakely, 1996), and the United States (Asgary & Segar, 2011; Shannon, Vinson, Cook, & Lennon, 2016), reported that refugee clients expected to be misunderstood because of the poor quality of interpretation services with some clients not receiving care because of the absence of interpretation services.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty publications discussed the impact of the low availability of adequate interpretation services on mental health access and service quality (Asgary & Segar, 2011; Bischoff et al, 2003; Blakely, 1996; Fegert et al, 2018; Fondacaro & Harder, 2014; Forrest-Bank, Held, & Jones, 2019; Hémono et al, 2018; Jensen, Norredam, Priebe, & Krasnik, 2013; Morland, Duncan, Hoebing, Kirschke, & Schmidt, 2005; Pian, Hoyez, & Tersigni, 2018). Studies from Greece (Hémono et al, 2018), New Zealand (Blakely, 1996), and the United States (Asgary & Segar, 2011; Shannon, Vinson, Cook, & Lennon, 2016), reported that refugee clients expected to be misunderstood because of the poor quality of interpretation services with some clients not receiving care because of the absence of interpretation services.…”
Section: Resultsmentioning
confidence: 99%
“…There exists precedent for nationally recognized professional standards and guidelines for mental health interpreting in other countries. For example, in France, a working group of non-profit organizations, including organizations that focus on mental health interpreting, has developed a charter for professional interpreting standards at the behest of the national health authority [34]. Practice guidelines for mental health interpreters have also been developed in Australia and are endorsed by national professional associations representing spoken and sign language interpreters [35].…”
Section: Discussionmentioning
confidence: 99%
“…These concerns suggest that providers did not always trust that interpreters were executing their role appropriately. Previous literature indicates that trust between providers and interpreters is a key factor for effective communication, more so in mental health than in any other setting [23,34].…”
Section: Discussionmentioning
confidence: 99%
“…En effet, de l'avis de professionnels médicaux et médico-sociaux interrogés dans une autre étude (Arend et al, 2017), les interprètes devraient être présents à différents moments clés d'intervention comme le diagnostic, le changement de traitement et la délivrance de médicaments. Pour certains domaines particuliers, comme celui de la santé mentale notamment, s'il n'y a pas d'interprète, le suivi est très difficile ou ne peut pas se faire (Pian et al, 2018).…”
Section: Réticences Freins Et Limites Au Déploiement De L'interprétariatunclassified
“…En effet, peinant à recruter des interprètes diplômés en interprétariat/traduction, peu intéressés par un métier demeurant somme toute précaire, et très souvent exercé à temps partiel imposé xvii , les associations salariant les interprètes puisent dans la demande d'emploi disponible. Cette double dynamique, étroitement insérée dans les contraintes structurelles du marché du travail, redouble les enjeux liés à la professionnalisation de la pratique : en effet, en l'absence d'un diplôme ou d'une formation dans le domaine de l'interprétariat et/ou la traduction en santé et social xviii , les savoir-faire des interprètes relèvent de premier abord de savoir-faire biographiques, liés à la maitrise d'une langue maternelle (Pian et al, 2018).…”
Section: Les Réalités Du Métier 34unclassified